Qualitative study of preferences and attitudes towards honey consumption in Hungary - Oravecz Titanilla (Analecta technica Szegedinensia, 2019)
Honey is becoming increasingly popular among consumers for its health and nutritional benefits as well as several other functions. The survey identifies four main dimensions of honey-purchasing motivation: medical benefits of honey consumption, dietary quality, cosmetics and sweetener. There are very limited empirical analysis of the aspects of honey consumption. The present study contributes to fill this knowledge gap through a qualitative study of consumer perceptions, preferences and attitudes towards honey among Hungarian consumers through 86 in-depth interviews. The study identifies different consumer segments, which are also willing to pay premium prices for the Hungarian or local honey. Quality cues are defined by search attributes of the product (colour, taste, aroma, thickness), and ethical attributes (warranties, brand name, country-of-origin).